Authoritarian backsliding and the concentration of political power. Issue 7 (9th November 2016) - Dresden, Jennifer Raymond; Howard, Marc Morjé
ABSTRACT: This article introduces the concept of authoritarian backsliding as a class of strategies for the concentration of incumbent political power in hybrid regimes. Such actions include manipulating elections, violating civil liberties, creating an extremely uneven playing field for the opposition, and reducing the institutional constraints on executive power. While often falling short of a full regime change, backsliding can significantly alter the level of political competition in a country and reduce the quality of its political life. This article develops a theoretically-grounded strategy to identify and measure backsliding events since 1989, showing that they have been much more common than is typically appreciated. The article also shows the utility of the concept of backsliding for better understanding regime stability. Using cross-national analysis of backsliding events from 1989–2004, we find that threats such as opposition electoral gains or economic crises in resource-dependent regimes create incentives for authoritarian backsliding.